Hadis Terbitnya Bintang Ṡurayyā Dalam Musnad Imam Ahmad Bin Hanbal (Studi Sanad Dan Matan Hadis) - Abi Hurairah (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
Starting from the Covid-19 virus outbreak that never went away, most of the partiesfelt suffering. Until it is natural that all groups really hope that this epidemic willdisappear soon. As was the excitement of the news circulating through the twitteraccount of one of the residents who argued that this covid-19 outbreak would endsoon when a star rose in the morning. This is based on information from the hadith ofthe Prophet صلى الله عليه وسلم in the history of Imam Ahmad bin Hanbal which states this. But inreality until now the Covid-19 outbreak is still there. The existence of this incident isfeared to raise suspicions among the public that not all the words of the prophet aretrue (lies). With this, the researcher focuses on two problem formulations. First, howis the quality of the sanad and matan of the hadith regarding the publication of theurayya star as a sign of the end of the plague, secondly, how is the content of thehadith. This study uses the takhrij wa dirāsah al-asanid method in the sanad, whilethe matan uses the Syarhu al-Had method. The approach used is historical with thetype of library research. The data collection methods used are takhrij, iʻtibar andSyarhu al-ḥadīṡ. The results of this study The Hadith about the rising of the urayyastar as a sign of the end of this plague is classified as asan Garib. If you look at thesanad, this hadith is classified as mutta'il. However, in terms of quality, this hadith isconsidered asan because there are narrators whose credibility does not meet therequirements of aḥīḥ hadith, namely Isl bin Sufyān al-Tamīmī al-Yarbūʻī, he isconsidered aʻīf. Because it only came from a friend of Ab Hurairah and then onlypivoted to Imam Ahmad bin Hanbal, this hadith is considered garb and includesabsolute garb. While the matan is not aḥīḥ because it does not meet the criteria foraḥīḥ-matan. This deficiency is contrary to the arguments of the Qur'an and commonsense. The content of this hadith is an explanation or information of the Prophetregarding the time of the disappearance of pests which is marked by the rising of thestar (Ṡurayyā) in the morning. But what must be underlined is that the word al-ʻĀhatuhere is not the Covid-19 (corona) outbreak or the plague in general, but disputes anddisputes between people at that time regarding the sale and purchase of fruits thatwere defective or damaged because it was not yet timed. to be harvested. The Prophetthen forbade this activity and made the publication of the urayya star as a benchmarkfor the resumption of buying and selling. This is because when the Ṡurayya star rises,according to custom in the Hijaz lands, it is the beginning of the harvest season,which in the end makes the sale and purchase dispute averted (lost/raised).